THE FERAL DETECTIVE : A Novel - Lethem, Jonathan, 1964- (New York, NY : Ecco, an imprint of HarperCollinsPublishers, 2018)
Convincing an enigmatic loner, Charles Heist, a.k.a. the Feral Detective, to help her search for a friend's missing daughter, Phoebe Siegler traverses the outskirts of California's stunning Inland Empire, where she discovers her companion's complicated relationship with warring tribes of outcasts
Keywords: Missing persons -- Fiction; Private investigators -- Fiction; Los Angeles, California -- Fiction; Mystery fiction; Detective and mystery fiction